Pembinaan Iman Jemaat: "Carilah Tuhan" Berdasarkan Kitab Amos 5: 4-6 di GBI Gunungsari Salatiga - Tantri Yulia (Journal Of Social Empowerment Publications, 2025)
The congregation at GBI Gunungsari Salatiga is a congregation that is experiencing faith growth, but this congregation faces challenges to prioritize God in personal, family and society. In order to overcome this, the pastor has a regular formation program through teaching the Word of God. This faith formation has the theme “Seek The Lord” based on the Book of Amos 5:4-6 on December 8, 2024 at 08.00-10.00 at GBI Gunungsari Salatiga. The presentation of this faith formation preparation was through exposition study and literature study of Amos 5:4-6. While the implementation of community service uses the lecture method. There are 3 main points that can be done by the congregation to face the challenge of prioritizing God through the theme 'Seek God'. First: the congregation must seek God, second: the congregation must seek God through repentance. Third: the congregation must seek God by putting God first. The result of this PkM is that the congregation understands the meaning of seeking God, the congregation experiences repentance as a response to seeking God and the congregation is committed to prioritizing God in the practice of daily life.